Apical External Root Resorption and Repair in Orthodontic Tooth Movement: Biological Events. (29th March 2016) - Feller, Liviu; Khammissa, Razia A. G.; Thomadakis, George; Fourie, Jeanine; Lemmer, Johan
Abstract : Some degree of external root resorption is a frequent, unpredictable, and unavoidable consequence of orthodontic tooth movement mediated by odontoclasts/cementoclasts originating from circulating precursor cells in the periodontal ligament. Its pathogenesis involves mechanical forces initiating complex interactions between signalling pathways activated by various biological agents. Resorption of cementum is regulated by mechanisms similar to those controlling osteoclastogenesis and bone resorption. Following root resorption there is repair by cellular cementum, but factors mediating the transition from resorption to repair are not clear. In this paper we review some of the biological events associated with orthodontically induced external root resorption.